THE DYNAMICS OF RELIGIOUS CONSCIOUSNESS: METHODOLOGICAL ASPECTS - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article describes the methodological aspect of the issue and focus patterns dynamics of religious consciousness, the basic approaches to this problem.